Brabant Biënnale 1989. - Bagen, Arthur; Beijers, Franca; Besems, Korrie; Boetzkes, Jos; Creyghton, L.J.A.D.; Kantelberg, Peter; Kemper, Margriet; Koene, Peter; Laurense, Toon; Maters, John; Mulders, Marc; Peters, Stijn; et al. (Eindhoven : Van Abbemuseum, 1989)
Bagen, Arthur ; Beijers, Franca ; van den Bergh, Reinout ; Besems, Korrie ; Boetzkes, Jos ; van Campenhout, Ad ; Creyghton, L.J.A.D. ; van den Heuvel, Frank ; Kantelberg, Peter ; Kemper, Margriet ; Koene, Peter ; Laurense, Toon ; Maters, John ; Mulders, Marc ; van der Noord, Ruurd ; Peeters, Stijn ; Salmon, Geoffrey ; van Seeters, Rian ; Strik, Elly ; Tukker, Teuny
biog., tent. [6 p.]
Nederlands
Brabant Biënnale 1989, Van Abbemuseum Eindhoven, 8 juli tm 3 september 1989
boek